Pengaruh Pemberian Ekstrak Buah Gandaria (Bouea macrophylla Griff) Terhadap Perubahan Ekspresi Gen CD36 Pada Otak Tikus Yang Diinduksi CCL4 (Karbon Tetraklorida) - Rana Wahyuni; Zahratul Idami (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to analyze the effect of gandaria fruit extract (Bouea macrophylla Griff.) on CD36 gene expression in the brains of CCl₄-induced rats (Rattus norvegicus). The experiment employed a completely randomized design consisting of five groups: negative control, positive control (CCl₄), and three treatment groups administered gandaria fruit extract at doses of 100, 150, and 200 mg/kgBW. CD36 gene expression was assessed using semi-quantitative PCR, normalized to the GAPDH reference gene, and analyzed based on band density using ImageJ software. Statistical analysis was performed using one-way ANOVA followed by post hoc testing at a significance level of p < 0.05. The results demonstrated that CCl₄ induction increased CD36 expression by 1.9-fold compared to the control group. Administration of gandaria fruit extract reduced CD36 expression relative to the CCl₄ group, with the lowest fold change observed at 100 mg/kgBW (1.08), while higher doses showed relatively increased expression but remained lower than the positive control. These findings indicate that gandaria fruit extract has the potential to modulate CD36 gene expression under CCl₄-induced oxidative stress conditions, with the most effective response observed at the lowest dose.